PENGEMBANGAN WISATA TEMATIK BERBASIS KULINER DI DESA WISATA SERANGAN - Semara, I Made Trisna; Arun Suwi Arianty, AA. Ayu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 10 No 2 (2022): Jurnal IPTA (December 2022)DO - 10.24843/IPTA.2022.v10.i02.p24, 2023)
Serangan Village is one of the tourist villages in Denpasar City. Serangan Tourism Village faces quite tough tourism challenges. The challenge is not maximizing local products as a tourist attraction. The purpose of this research is to develop the concept of culinary-based thematic tourism in Serangan Tourism Village. The development of the thematic tourism concept is expected to encourage the development of Serangan Village as a tourist village by developing local food to become a tourist attraction. This concept is able to respond to global tourism trends and as a preservation of local cultural values. So that a tourist attraction will appear in the form of a culinary tour with the characteristics of Serangan Village or Bali in general. The research method uses a qualitative descriptive approach.